Bilateral pulmonary varicosities associated with coarctation of the aorta. Issue 1 (January 1970) - Rizk, Ghassan; Melhem, Rafik; Dagher, Ibrahim
Abstract : Varicosities of the pulmonary vein are rare. Twenty-eight cases confirmed anatomically or by angiography have been reported. In this paper the authors report a rather unique patient who had bilateral varices of the lungs in conjunction with coarctation of the aorta. The plain film and angiographic features of pulmonary varices are discussed. A brief review of the cases reported previously is also presented.